Sequence Requirements of Intrinsically Fluorescent G-Quadruplexes - Majerová, Tat'ána; Streckerová, Tereza; Bednárová, Lucie; Curtis, Edward A (Biochemistry, 2018)
G-Quadruplexes are four-stranded nucleic acid structures typically stabilized by GGGG tetrads. These structures are intrinsically fluorescent, which expands the known scope of nucleic acid function and raises the possibility that they could eventually be used as signaling components in label-free sensors constructed from DNA or RNA. In this study, we systematically investigated the effects of mutations in tetrads, loops, and overhanging nucleotides on the fluorescence intensity and maximum emission wavelength of >500 sequence variants of a reference DNA G-quadruplex. Some of these mutations modestly increased the fluorescence intensity of this G-quadruplex, while others shifted its maximum emission wavelength. Mutations that increased the fluorescence intensity were distinct from those that increased the maximum emission wavelength, suggesting a trade-off between these two biochemical properties. The fluorescence intensity and maximum emission wavelength were also correlated with multimeric state: the most fluorescent G-quadruplexes were monomers, while those with the highest maximum emission wavelengths typically formed dimeric structures. Oligonucleotides containing multiple G-quadruplexes were in some cases more fluorescent than those containing a single G-quadruplex, although this depended on the length and sequence of the spacer linking the G-quadruplexes. These experiments provide new insights into the properties of fluorescent G-quadruplexes and should aid in the development of improved label-free nucleic acid sensors.
Keywords: fluorescence; fluorescenční barviva; Fluorescence; DNA; sekvence nukleotidů; Fluorescent Dyes; Base Sequence; G-kvadruplexy; Dimerization; mutace; Mutation; oligonukleotidy; Oligonucleotides; Spectrometry, Fluorescence; fluorescenční spektrometrie; dimerizace; G-Quadruplexes